Perceived stress is inversely related to ideal cardiovascular health: The Paris Prospective Study III. (1st November 2018) - Poirat, L.; Gaye, B.; Perier, M.C.; Thomas, F.; Guibout, C.; Climie, R.E.; Offredo, L.; Tafflet, M.; Lemogne, C.; Pannier, B.; Boutouyrie, P.; Jouven, X.; et al.
Abstract: Background: We hypothesized that subjects with a high level of perceived stress would be less likely to have ideal cardiovascular health (CVH). Methods: CVH was estimated using the 7-item tool developed by the American Heart Association. Perceived stress was measured using the validated 4-item Perceived Stress Scale at baseline and after 4 years of follow-up. Linear and polytomous logistic regression analysis were conducted. Results: 8914 volunteers (38% women) free from a history of cardiovascular disease and aged 50 to 75 were recruited in the framework of The Paris Prospective Study III between 2008 and 2012. At baseline, higher perceived stress was associated with lower global CVH score (regression coefficient of highest vs. lowest quartile of perceived stress: β: −0.20, p < 0.001). Perceived stress was associated only with the behavioral CVH score (smoking, physical activity, diet, body mass index) but not the health CVH score (fasting glycemia, total cholesterol, blood pressure, smoking). On the other hand, higher global CVH score at baseline was associated with lower level of perceived stress (OR for being in the highest vs. the lowest quartile of perceived stress per unit increase in the CVH score: 0.95; CI 95%: 0.93; 0.98). Again, the association only existed for the behavioral CVH score. Finally, baseline behavioral CVH score was inversely associated with perceived stress at 4 years, even after adjustment for perceived stress measured at baseline (p < 0.001). Conclusion: Our study demonstrates a clear association between higher perceived stress and lower CVH, in particular behavioral CVH, which has implications for CVD prevention. Clinical Trial Registration :NCT00741728 Highlights: Higher level of perceived stress is inversely related to lower global cardiovascular health score. Higher global score is inversely related to lower level of perceived stress at baseline and on follow-up. These associations only exist for behavioral CVH score and not for health CVH score.